Etika Guru dalam Konteks Global: Studi Perbandingan Antara Profesionalisme Pendidik di Finlndia dan Guru Madrasah di Indonesia - Selvi Yulianis; Rahmatul Zikri Amalia; M. Ainurrafiq; Nadea Pratiwi; Aprizal Ahmad (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study explores the ethics of teachers in a global context by comparing the professionalism of educators in Finland and madrasah teachers in Indonesia. The research aims to identify key ethical principles and practices that define teacher professionalism in these distinct educational settings. Employing qualitative methods including literature review and interviews with educators from both countries, the study highlights similarities and differences in ethical standards, pedagogical approaches, and cultural influences. Findings reveal that while Finnish teachers emphasize autonomy, democratic values, and continuous professional development, Indonesian madrasah teachers integrate religious ethics alongside pedagogical professionalism. The study discusses implications for improving teacher training and ethical guidelines to enhance educational quality and foster intercultural understanding. This comparative analysis contributes to the global discourse on teacher ethics by providing insights into how cultural and institutional contexts shape professional values and responsibilities in education.